The Routledge companion to the work of John R. Rickford - Blake, Renée; Buchstaller, Isabelle (Routledge, 2020)
Cover; Half Title; Title; Copyright; CONTENTS; Acknowledgments; Contributors; John R. Rickford Publications; PART I Introduction; 1 Introduction to the Volume; 2 The Makings of a Linguist: John R. Rickford's Education in His Native Guyana; PART II Exploring Language Contact From a Sociolinguistic and Sociohistorical Point of View; 3 Introduction; 4 In the Fisherman's Net: Language Contact in a Sociolinguistics Context; 5 African-Indian-American South and Caribbean Worlds: Connecting With John R. Rickford's Language Contact Research
Includes bibliographical references and index
Keywords: Rickford, John R. -- 1949-; Sociolinguistics; Languages in contact; Language and culture; LANGUAGE ARTS & DISCIPLINES; Linguistics; Aufsatzsammlung